2021
DOI: 10.1016/s2589-7500(21)00082-0
|View full text |Cite
|
Sign up to set email alerts
|

An integrated nomogram combining deep learning, Prostate Imaging–Reporting and Data System (PI-RADS) scoring, and clinical variables for identification of clinically significant prostate cancer on biparametric MRI: a retrospective multicentre study

Abstract: Background Biparametric MRI (comprising T2-weighted MRI and apparent diffusion coefficient maps) is increasingly being used to characterise prostate cancer. Although previous studies have combined Prostate Imaging-Reporting & Data System (PI-RADS)-based MRI findings with routinely available clinical variables and with deep learning-based imaging predictors, respectively, for prostate cancer risk stratification, none have combined all three. We aimed to construct an integrated nomogram (referred to as ClaD) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
83
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 31 publications
2
83
0
Order By: Relevance
“…12/28 papers deployed fully-automated AI methods based on DL methods and were therefore screened using CLAIM, while 16/28 papers used TML methods to develop semi-automated AI approaches and were assessed using RQS. Of these, 5/12 (42%) DL papers [ 20 24 ] and 12/16 (43%) TML papers [ 25 36 ] passed the quality screening and were subject to full QUADAS-2 assessment, data extraction, and narrative synthesis.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…12/28 papers deployed fully-automated AI methods based on DL methods and were therefore screened using CLAIM, while 16/28 papers used TML methods to develop semi-automated AI approaches and were assessed using RQS. Of these, 5/12 (42%) DL papers [ 20 24 ] and 12/16 (43%) TML papers [ 25 36 ] passed the quality screening and were subject to full QUADAS-2 assessment, data extraction, and narrative synthesis.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…None of the papers performed phantom studies to detect scanner-dependent features (Q3), reported calibration statistics (Q10), registered a prospective study (Q11), and reported on the cost-effectiveness of the clinical application of the proposed models (Q14). Only one (8%) paper [ 32 ] discussed a potential biological correlate for some radiomic features included in the final model (Q7), and only two papers [ 28 , 36 ] performed external testing of their models (Q12). Furthermore, only six out of 12 (50%) papers [ 25 , 26 , 29 32 ] had image segmentation performed by multiple radiologists or instead assessed the robustness of radiomic features to ROI morphological perturbations (Q2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations